2014
DOI: 10.3390/molecules19021603
|View full text |Cite
|
Sign up to set email alerts
|

A New Dicoumarinyl Ether from the Roots of Stellera chamaejasme L

Abstract: Abstract:A new dicoumarinyl ether, 3-hydroxy-6-methoxy-7,7'-dicoumarinyl ether (1), was isolated from the roots of Stellera chamaejasme L, together with the known compound umbelliferone (2). Their structures were determined on the basis of spectroscopic techniques, including IR, NMR, and HR-ESI-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Its roots are commonly known as ‘Ruixianglang du’ in Chinese, and have been used in China as a traditional Chinese medicine for the treatment of scabies, tinea, stubborn skin ulcers, chronic tracheitis, cancer and tuberculosis (Xu, Qin, Li, & Xu, ; Zhang et al, ; Pan et al, ). Previous phytochemical studies of S. chamaejasme L. have shown that it contains various kinds of chemical components, including diterpene, lignans, coumarins, phenylpropanoid, flavonoids and volatile oil (Li, Shen, Bao, Chen, & Li, ; Yan et al, ; Zhang et al, ). Modern studies have suggested that flavonoids from S. chamaejasme L. are the main components that mostly contribute to the pharmacological efficacy (Liu et al, ; Liu & Zhu, ; Liu, Han, et al, ; Liu, Yang, et al, ), such as anti‐cancer activity (Liu et al, ; Li, Zhang, Pang, ZhengChen, & Gan, ), anti‐fatty liver (Wang, Li, Han, Wang, & Li, ) and anti‐HIV (Asada et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Its roots are commonly known as ‘Ruixianglang du’ in Chinese, and have been used in China as a traditional Chinese medicine for the treatment of scabies, tinea, stubborn skin ulcers, chronic tracheitis, cancer and tuberculosis (Xu, Qin, Li, & Xu, ; Zhang et al, ; Pan et al, ). Previous phytochemical studies of S. chamaejasme L. have shown that it contains various kinds of chemical components, including diterpene, lignans, coumarins, phenylpropanoid, flavonoids and volatile oil (Li, Shen, Bao, Chen, & Li, ; Yan et al, ; Zhang et al, ). Modern studies have suggested that flavonoids from S. chamaejasme L. are the main components that mostly contribute to the pharmacological efficacy (Liu et al, ; Liu & Zhu, ; Liu, Han, et al, ; Liu, Yang, et al, ), such as anti‐cancer activity (Liu et al, ; Li, Zhang, Pang, ZhengChen, & Gan, ), anti‐fatty liver (Wang, Li, Han, Wang, & Li, ) and anti‐HIV (Asada et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The 35 known analogues ( 14 – 48 ) were identified as umbelliferone ( 14 ), 7-coumarincarboxaldehyde ( 15 ), isoscopoletin ( 16 ), murralonginal ( 17 ), xanthyletin ( 18 ), nordentatin ( 19 ), 1-hydroxybisabola-2,10-dien-4-one ( 20 ), methyl 3- O -feruloylquinate ( 21 ), 2-( p -hydroxyphenyl)­ethyl p -coumarate ( 22 ), 4-hydroxy-3-(3-methyl-2-butenyl)­cinnamyl alcohol ( 23 ), murpanicin ( 24 ), coumurrayin ( 25 ), sibiricol ( 26 ), osthol ( 27 ), trans -dehydroosthol ( 28 ), gleinadiene ( 29 ), 1′-isovalerylmurrangatin ( 30 ), 2′- O -ethylmurrangatin ( 31 ), osthenon ( 32 ), sibirinol ( 33 ), 5,7-dimethoxy-8-(3-ethoxy-2-hydroxy-3- methylbutyl)­coumarin ( 34 ), cis -osthenon ( 35 ), toddalenone ( 36 ), murrangatin ( 37 ), omphalocarpin ( 38 ), auraptenol ( 39 ), (−)-mexoticin ( 40 ), , murracarpin ( 41 ), (−)-murracarpin ( 42 ), minumicrolin ( 43 ), minumicrolin isovalerate ( 44 ), murrangatin isovalerate ( 45 ), isomurralonginol nicotinate ( 46 ), toddalosin ( 47 ), and cladimarin B ( 48 ) by comparison of their observed and reported spectroscopic data.…”
Section: Resultsmentioning
confidence: 99%
“…This was determined as the HMBC spectrum showed that H-2' and H-6'(δ H 7.11) correlated with C-2 (δ C 81.8), H-2"' and H-6"' (δ H 6.92) correlated with C-2" (δ C 83.5), and H-2""' and H-6""' (δ H 7.01) correlated with C-2"" (δ C 82.8) (Figure 2 Compounds 2-10 (Figure 1) were identified using different spectroscopic techniques and by comparing the resulting data with the data published in the literature. The compounds were identified as daphnoretin methyl ether (2) [27], rutamontine (3) [28], neodaphnoretin (4) [29], acetyl daphnoretin (5) [30], edgeworthin (6) [27], genkwanin (7) [31,32], trans-tiliroside (8) [33], p-Hydroxybenzoic acid (9) [34] and β-sitosterol glucoside (10) [35].…”
Section: Identification Of Compounds 1-10mentioning
confidence: 99%